Camk2a suppresses denervated muscle atrophy by maintaining the Ca2+ homeostasis in muscle cells: Overexpression of Camk2a inhibits denervated muscle atrophy - Zhang, Yanan; Xia, Mingjie; Zhao, Tianyu; Zhang, Qinyang; Li, Rulin; Yang, Lei (Cellular and Molecular Biology, 2023)
Denervated muscle atrophy is a severe neurological complication that significantly impacts patients' quality of life. Currently, there is a lack of effective treatment methods. This study aims to investigate the molecular mechanisms associated with denervated muscle atrophy and explore potential therapeutic targets. In this study, we assessed the severity of denervated muscle atrophy by measuring the wet-weight ratio of the calf muscles. We conducted Western blot and immunofluorescence experiments to observe the morphology and cross-sectional area of muscle fibers following sciatic nerve transection. Simultaneously, we evaluated the expression of Camk2a in muscle tissue and measured changes in Ca2+ using the BCA method. Additionally, we performed HE and Sirius Red staining on denervated muscle tissue to observe the cross-sectional area of muscle fibers and collagen deposition in response to Camk2a overexpression. In our study, We observed a significant decrease in the wet weight ratio of the muscles, myosin, and muscle fiber cross-sectional area with the prolonged duration of sciatic nerve transection. Subsequently, we observed varying degrees of elevation in Ca2+ levels in denervated muscle tissue, while Camk2a, which regulates Ca2+ signal transduction, significantly decreased in denervated muscle tissue. Overexpression of Camk2a reduced the accumulation of Ca2+ in muscle tissue, resulting in higher muscle wet weight ratios, larger muscle fiber cross-sectional areas, and a significant reduction in collagen deposition in muscle tissue. In conclusion, our study provides the first evidence that Camk2a can alleviate calcium overload in muscle cells and ameliorate denervated muscle atrophy. Our findings suggest that Camk2a may serve as a crucial regulatory target in denervated muscle atrophy.